Evaluación de especies gramíneas locales para la remediación de suelos contaminados por metales pesados en la empresa Triboilgas - Catagña Niza, Juan Alberto (2016)
The objective of the present work was to evaluate the capacity the phytoremediation of three gramineous species: Guinea (Panicum maximum), Marandu (Brachiaria brizantha) and Mombasa (Panicum maximun), in soil contaminated with hydrocarbons in the community of Flower of the marsh, Province of Orellana. Delimited the area of study was an analysis of the concentration in the soil of 5 of heavy metals, cadmium, lead, cobalt, mercury and total chromium. The result showed that four of them met the permissible maximum values as opposed to the total chromium that exceeded the values. Introduced species grew over 3 months (90 days), after this period was carried out an analysis of the total chromium in soil, to know the extraction capacity of the contaminant total chromium in different trials.